2010
DOI: 10.1021/es101088k
|View full text |Cite
|
Sign up to set email alerts
|

Binding Strength of Methylmercury to Aquatic NOM

Abstract: A competitive-ligand, equilibrium-dialysis technique using bromide measured methylmercury (MeHg(+)) binding to Suwannee River fulvic acid (SRFA) and NOM from a lake and a bog in Minnesota. Distribution coefficients (K(OC)) and stability constants (K') varied only slightly over a range of [Br(-)] and ratios of MeHg(+) to reduced sulfur, S(re), the putative NOM binding site. For SRFA at pH 3.0, K(OC) ranged from 10(7.7) to 10(8.2) and K' ranged from 10(15.5) to 10(16.0) over MeHg(+):S(re) ratios from 1:1220 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…However, Gemmatimonadetes was stimulated by the longterm Hg stress, and a similar pattern was also observed along copper gradient under long-term field exposure (unpublished data). One possible reason for this result could be that metal stress severely affects sensitive species [54] and decreases their competition ability, resulting in an increase in the relative abundance of metal-resistant species to maintain ecological stability [46]. Similar patterns were found in the order of Anaerolineales, envOPS12, SBR1031, and Hydrogenophilales, whose abundances increased with elevated THg and MeHg concentrations.…”
Section: Effects Of Hg Contamination On the Distribution Of Bacterialmentioning
confidence: 58%
See 1 more Smart Citation
“…However, Gemmatimonadetes was stimulated by the longterm Hg stress, and a similar pattern was also observed along copper gradient under long-term field exposure (unpublished data). One possible reason for this result could be that metal stress severely affects sensitive species [54] and decreases their competition ability, resulting in an increase in the relative abundance of metal-resistant species to maintain ecological stability [46]. Similar patterns were found in the order of Anaerolineales, envOPS12, SBR1031, and Hydrogenophilales, whose abundances increased with elevated THg and MeHg concentrations.…”
Section: Effects Of Hg Contamination On the Distribution Of Bacterialmentioning
confidence: 58%
“…On the other hand, the different OM values among the four sites themselves might overshadow the impact of THg on microbial communities. It is highly possible since OM might not only furnish more substrate for microbes but also inhibit the toxicity of Hg especially MeHg by complexation [46]. Therefore, the significant positive correlation between MeHg and bacterial abundance (Fig.…”
Section: Effects Of Hg Contamination On the Diversity Abundance Andmentioning
confidence: 99%
“…High SO 4 2− content in the soils examined might be helpful to the prevalence of some SRM that produced MeHg (Han et al 2010), and this could explain partially why the SO 4 concentration are significantly correlated to the MeHg content. It was also suggested that OM can form strong complexes with MeHg + (Khwaja et al 2010), which would be absorbed and fixed on soil. The correlation between the contents of MeHg and OM in the paddy soils might further support the previous observation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Hg-NOM complexes, MeHg forms a linear two-coordinated complex with one Hg-C bond of 2.05Å (the bonding between the methyl group and mercury within the methyl mercury molecule) and one Hg-S bond of 2.35Å with the thiol group (Qian et al, 2002;Yoon et al, 2005). The number of CLE studies on MeHg-NOM interactions is smaller than for Hg (Hintelmann et al, 1997;Amirbahman et al, 2002;Karlsson and Skyllberg, 2003;Khwaja et al, 2010), but since the affinity of MeHg is lower, the methodological problems are less expressed and results are quite consistent. Even if many studies report results pointing at a complex formation with thiols in DOM and particulate NOM from soils, few have actually measured these groups.…”
Section: Complex Formation With Natural Organic Mattermentioning
confidence: 99%
“…Even if many studies report results pointing at a complex formation with thiols in DOM and particulate NOM from soils, few have actually measured these groups. Karlsson and Skyllberg (2003) and Khwaja et al (2010) made independent determinations of RSH groups using S XANES and calculated stability constants at MeHg to RSH molar ratios less than 2 × 10 −6 and 8 × 10 −3 , respectively. Using a model with pK a = 9.96 (similar to mercaptoacetic acid), a log K in the range 15.6 (pH 5.1)-17.1 (pH 2.0) at 0.25 M ionic strength (Karlsson and Skyllberg, 2003), and 15.5-16.0 at pH 3 and I = 0 (Khwaja et al, 2010), was reported for the reaction MeHg + + RS − = MeHgSR in an organic soil and Suwanee River fulvic acid, respectively.…”
Section: Complex Formation With Natural Organic Mattermentioning
confidence: 99%